The effect of temperature and moisture on the physical and chemical stability of paracetamol tablets (500 mg) marketed in Syria - Mansour, Oussama (Latakia University Journal -Medical Sciences Series, 2018)
Stability is an essential factor of quality, safety and efficacy of a drug product. The objective of this study was to investigate the effect of moisture and temperature on paracetamoltablets (500 mg) marketed in Syria. Three commercial brands (A, B, C) were examined.Tablets were exposed to different storage conditions (RH=75%& 40°C) , (RH=75%& 25°C), (RH=60%& 40°C), (RH=60%& 25°C) for 6 months and storage on shelf for 12 months. Changes in physicochemical properties of tablets were determined by hardness, friability tests and assay the content. High humidity and temperature (RH=75%& 40°C) decreased in hardness and content of paracetamol tablets( less than 90%) and increased in friability (more than 1%) in all studied brands. Second condition also caused the same results, but less than the first condition because of normal temperature. The effect of temperature on stability is less than moisture as we saw in the third condition (RH=60%& 40°C).physicochemical properties of tablets remainedwithout changes when stored in (RH=60%& 25°C) condition. The storage of tablets on shelf caused changes in hardness , friability, and content of tablets according to climatic changes during the year. تأثير درجة الحرارة والرطوبة على ثباتية الخصائص الفيزيائية والكيميائية لأقراص الباراسيتامول (500 مغ) المسوقة في سوريا الثباتية هي عامل أساسي لجودة وسلامة وفعالية المنتج الدوائي و أن الهدف من هذا البحث هو دراسة تأثير الرطوبة ودرجة الحرارة على أقراص الباراسيتامول (500 مغ) التي يتم تسويقه في سورية. تم فحص ثلاث أصناف تجارية (A، B، C). (درجة رطوبة = 75٪ وحرارة 40 درجة مئوية)، (ودرجة رطوبة = 75٪ وحرارة 25 درجة مئوية)، (درجة رطوبة = 60٪ وحرارة 40 درجة مئوية)، (درجة رطوبة = 60٪ وحرارة 25 درجة مئوية) لمدة 6 أشهر والتخزين على الرف لمدة 12 شهرا. تم تحديد التغيرات في الخصائص الفيزيوكيميائية للأقراص عن طريق اختبارات القساوة، واختبارات التفتت وفحص المحتوى. أنقصت الرطوبة العالية ودرجة الحرارة (درجة رطوبة = 75وحرارة 40 درجة مئوية) في قساوة ومحتوى أقراص الباراسيتامول (أقل من 90٪) وزادت في القابلية للتفتت (أكثر من 1٪) في جميع الأصناف التجارية المدروسة. أعطى الشرط الثاني من الرطوبة والحرارة بنفس النتائج، ولكن أقل من الشرط الأول بسبب درجة الحرارة العادية. وكان تأثير درجة الحرارة على الثباتية أقل من الرطوبة كما هو في الشرط الثالث (درجة رطوبة = 60٪ وحرارة 40 درجة مئوية). بقيت الخصائص الفيزيوكيميائية للأقراص دون تغييرات عند تخزينها في (درجة رطوبة = 60٪ وحرارة 25 درجة مئوية). وتسبب تخزين الأصناف على الرف في حدوث تغيرات في القساوة، والتفتت، ومحتوى الأقراص وفقا للتغيرات المناخية خلال السنة.